Genetics of phenylketonuria: then and now - Blau, Nenad (Human mutation, 2016)
More than 950 phenylalanine hydroxylase (PAH) gene variants have been identified in people with phenylketonuria (PKU). These vary in their consequences for the residual level of PAH activity, from having little or no effect to abolishing PAH activity completely. Advances in genotyping technology and the availability of locus-specific and genotype databases have greatly expanded our understanding of the correlations between individual gene variant, residual PAH activity, tetrahydrobiopterin (BH4) responsiveness, and the clinical PKU phenotype. Most patients (∼76%) have compound heterozygous PAH gene variants and one mutated allele may markedly influence the activity of the second mutated allele, which in turn may influence either positively or negatively the activity of the biologically active heterotetrameric form of the PAH. While it is possible to predict the level of BH4 responsiveness (∼71%) and PKU severity (∼78%) from the nature of the underlying gene variants, these relationships remain complex and incompletely understood. A greater understanding of these relationships may increase the potential for individualized management of PKU in future. Inherited deficiencies in BH4 metabolism account for about 1%-2% of all hyperphenylalaninemias and are clinically more severe than PKU. Almost 90% of all patients are deficient in 6-pyruvoyl-tetrahydropterin synthase and dihydropteridine reductase.